Energy Transfer Efficiency from ZnO-Nanocrystals to Eu(3+) Ions Embedded in SiO(2) Film for Emission at 614 nm - Mangalam, Vivek (Materials (Basel), 2017)
In this work, we study the energy transfer mechanism from ZnO nanocrystals (ZnO-nc) to Eu(3+) ions by fabricating thin-film samples of ZnO-nc and Eu(3+) ions embedded in a SiO(2) matrix using the low-cost sol-gel technique. The time-resolved photoluminescence (TRPL) measurements from the samples were analyzed to understand the contribution of energy transfer from the various ZnO-nc emission centers to Eu(3+) ions. The decay time obtained from the TRPL measurements was used to calculate the energy transfer efficiencies from the ZnO-nc emission centers, and these results were compared with the energy transfer efficiencies calculated from steady-state photoluminescence emission results. The results in this work show that high transfer efficiencies from the excitonic and Zn defect emission centers is mostly due to the energy transfer from ZnO-nc to Eu(3+) ions which results in the radiative emission from the Eu(3+) ions at 614 nm, while the energy transfer from the oxygen defect emissions is most probably due to the energy transfer from ZnO-nc to the new defects created due to the incorporation of the Eu(3+) ions.